SHARIAH-COMPLIANT VENTURE CAPITAL: EXPLORING FINANCING MODELS FOR STARTUPS IN INDONESIA - Gusti Dewi; Aylin Erdogan; Ammar Al-Momani (Sharia Oikonomia Law Journal, 2025)
The rise of startups in Indonesia has created a growing demand for innovative financing models that align with Shariah principles. Shariah-compliant venture capital (SCVC) offers a unique opportunity to support startups while adhering to Islamic ethical standards, such as the prohibition of riba (interest) and gharar (uncertainty). This study explores the potential of SCVC as a financing model for startups in Indonesia, focusing on its alignment with Shariah principles, its impact on startup growth, and the challenges faced by stakeholders. The research aims to identify effective strategies for implementing SCVC and propose recommendations for enhancing its role in fostering ethical and sustainable entrepreneurship. Using a mixed-methods approach, this study combines quantitative analysis of startup financing data with qualitative interviews with venture capitalists, Shariah scholars, and startup founders. Data were analyzed to assess the compatibility of SCVC with Shariah principles, its financial performance, and its contribution to startup success. The findings reveal that SCVC can effectively support startups while adhering to Islamic ethics, but challenges such as limited awareness, regulatory gaps, and risk-sharing complexities hinder its widespread adoption. The study concludes that promoting SCVC in Indonesia requires targeted strategies, including education, regulatory reforms, and capacity-building for stakeholders.